CP ANGLE MEDULLOBLASTOMA WITH SUPRATENTORIAL DROP METS - Razzaq, Sana; Muhammad Assad Javed,; Ain Us Saba,; Niaz Ahmed,; Salman Habib,; Sana Razzaq, (Journal of Ayub Medical College Abbottabad, 2024)
Medulloblastoma, is an undifferentiated neuroepithelial tumour of embryonic origin. It is an uncommon central nervous system tumour, and adult-onset is even rarer. It could form in an unusual or unconventional location, like the cerebellopontine angle (CPA), and such tumours don't frequently show supratentorial extension. Less than 2 per million persons are affected each year, with children being affected ten times more than adults. Case Presentation: We present a 17-year-old male with complaints of occipital headache and having trouble walking for three months. Right Cerebellopontine (CP) angle lesion with ipsilateral mass effect over the cerebellum was seen on MRI brain with contrast. The tumour was excised by right sub-occipital retro mastoid craniotomy and histopathology revealed medulloblastoma. Post-operatively patient underwent chemo-radiotherapy. Craniospinal MRI was done to look for any dropmets. Recovery was uneventful. Two years later, he complained about headaches and generalized tonic-clonic seizure, MRI brain with contrast revealed a lesion with extra-axial components with a mass effect in the right temporal lobe. Right temporal craniotomy was done and the tumour was excised and histopathology showed a round blue cell tumour (medulloblastoma). Conclusion: We report a rare case of medulloblastoma located at the CP angle along with supratentorial metastasis 2-years after treatment.